Textbook of cardiovascular intervention - Thompson, Craig A. (Editor) (London Springer, 2014)
Catheter-based interventions have evolved to address a variety of needs through innovation and clinical evidence. The field of interventional cardiology and interventional vascular medicine now comprises the dominant diagnostic and therapeutic field within cardiovascular medicine and continues to grow in terms of patients managed and physicians trained. Given the vast expansion of technologies, techniques, and the clinical evidence base, it can be challenging for the practicing clinician, fellow-in-training, or technology developer to maintain general knowledge of the interventional cardiovascular field. The Textbook of Cardiovascular Intervention is intended to provide a practical, comprehensive and compact text on interventional cardiology for the current, rapidly evolving practice environment. It will appeal to fellows, residents and physicians in cardiology, interventional cardiology, cardiothoracic and vascular surgery, vascular and endovascular medicine, neurointerventional radiology and surgery, emergency medicine and intensive care
Invasive Hemodynamic.- Optimal Angiographic Technique and Quantitative Analysis.- Quantitative, Qualitative, and Diagnostic Intravascular Ultrasound.- Patient Selection for Coronary Intervention.- Contrast Nephropathy and Kidney Injury.- Vascular Access, Closure, and Management.- The Transracial Approach for Coronary Angiography and Intervention.- Guidewires and Angioplasty Balloons: The Primer.- Coronary Atherectomy (Rotational, Laser, Directional) and Thrombus Extraction.- Stents: Safety and Efficacy.- Adjunctive Pharmacology for Coronary Intervention.- Robotic Assisted Coronary Intervention.- The Transracial Approach for Coronary Angiography and Intervention.- Percutaneous Cell Therapy for Acute and Chronic Cardiac Disease.- Physiologic Evaluation of Patients with Ischemic Heart Disease.- Interventional Management of Acute Myocardial Infarction.- Hemodynamic Support in PCI: From Chronic Heart Failure to Cardiogenic Shock.- PCI Considerations in Women: Gender Specific Outcomes and Challenges.- Percutaneous Coronary Interventions in the Elderly.- Left Main PCI: Patient Selection and Technique.- Multivessel Disease.- Coronary Bifurcation Lesions.- Chronic Total Occlusion Angioplasty: Indications, Appropriateness, and Strategy.- The Retrograde Approach To Chronic Total Occlusion PCI.- Intravascular Ultrasound Applications for Chronic Total Occlusion Percutaneous Intervention.- Percutaneous Mitral and Aortic Balloon Valvuloplasty.- Transcatheter Aortic Valve Therapy.- Percutaneous Management of Mitral Regurgitation.- Upper Extremity Interventions.- Percutaneous Management of Lower Extremity Arterial Disease: Patient Selection, Techniques, and Technologies.- Application of Advanced Technologies for the Treatment of Lower Extremity Arterial Disease.- Percutaneous Management of Renovascular Diseases.- Endovascular Therapy for Mesenteric Disease.- Endovascular Management of Aortic Aneurysmal and Stenotic Disease.- Percutaneous Management of Carotid and Vertebral Artery Disease.- Acute Stroke Intervention.- Venous Thromboembolic Disease
Keywords: Cardiovascular Diseases therapy; Cardiovascular system Diseases Treatment